2019
DOI: 10.1002/acn3.50951
|View full text |Cite
|
Sign up to set email alerts
|

Default mode network anatomy and function is linked to pediatric concussion recovery

Abstract: ObjectiveTo determine whether anatomical and functional brain features relate to key persistent post–concussion symptoms (PPCS) in children recovering from mild traumatic brain injuries (mTBI), and whether such brain indices can predict individual recovery from PPCS.MethodsOne hundred and ten children with mixed recovery following mTBI were seen at the concussion clinic at Neurology department Alberta Children’s Hospital. The primary outcome was the Post–Concussion Symptom Inventory (PCSI, parent proxy). Sleep… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 54 publications
2
27
1
Order By: Relevance
“…Echo-planar images (rs-fMRI) were collected for five minutes and ten seconds (2000 ms TR, 30 ms TE, 90° flip angle, 3.6 mm slice thickness, 23 × 23 cm FOV, 64 × 64 matrix). As reported elsewhere, 9, 21 pre-processing included regression of nuisance covariates including head motion (Friston 24), linear trends, and signals from cerebrospinal fluid (CSF) and white matter (WM). Our final cohort comprised of a total of 62 subjects, after excluding 6 subjects due to absence of post-treatment scans or failure to pass quality control measures.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Echo-planar images (rs-fMRI) were collected for five minutes and ten seconds (2000 ms TR, 30 ms TE, 90° flip angle, 3.6 mm slice thickness, 23 × 23 cm FOV, 64 × 64 matrix). As reported elsewhere, 9, 21 pre-processing included regression of nuisance covariates including head motion (Friston 24), linear trends, and signals from cerebrospinal fluid (CSF) and white matter (WM). Our final cohort comprised of a total of 62 subjects, after excluding 6 subjects due to absence of post-treatment scans or failure to pass quality control measures.…”
Section: Methodsmentioning
confidence: 99%
“… A) Pre-melatonin GM clusters in the PCC (indicated in red, from our previous study 9 ) were identified from whole-brain analyses to be negatively correlated with sleep and fatigue disturbances. The main effect of group of whole-brain GM post-melatonin in this study is also shown (indicated in bright green).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations